THE INDIGENOUS EXPERIENCE: REPRESENTATIONAL SOVEREIGNTY AND RECONCILIATION IN CANADIAN URBAN SPACE - Karen Wall, (PEOPLE: International Journal of Social Sciences, 2025)
Urban indigenous spaces may be characterized by tangible and intangible cultural phenomena including art and architecture. Following Canada’s Truth and Reconciliation Report in 2015, Canadian municipalities have pursued various paths toward inclusion of Indigenous voices in city planning. This paper examines manifestations of Indigenous cultural presence in the city of Edmonton, home to the second largest and growing urban Indigenous population in the country. In the development of a mature postcolonial civic identity, both formal and informal interventions into public space can support transformative, dialogic, cross-cultural encounters. But do civic investments in visible and discursive media promote or undermine genuine representational sovereignty and reconciliation in the ongoing context of Indigenous struggles for social and economic equity? The discussion is situated in an analytical framework including the right to the city, biopolitics and media ecology. Indigenous presence in public art and urban spaces are discussed with reference to both sanctioned or sponsored and informal, transient public art, murals, graffiti and constructions in everyday space and on sacred ground in the city. It concludes with analysis of a new, award-winning multi-media “Indigenous Experience” installation in the city’s touristic heritage park in the context of the calls to action of the Truth and Reconciliation Report of almost ten years ago.